Basketball Flashback at Regional Student Sports Week (Popwil): Coaching and Achievement Study - Anggie Sugiarto; Aam Ali Rahman; Ayi Suherman; Adang Sudrazat; Dewi Susilawati (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This research examines the coaching expedition and results of Sumedang Regency's student basketball teams in the Regional Student Sports Week (POPWIL) competition, addressing the limited historical selection and the limited global mapping of student-level sports coaching systems. The research framework is based on the importance of POPWIL as a marker of the effectiveness of regional sports coaching and as a bridge to larger competitions. The research aims to reconstruct Sumedang's student basketball coaching model, identify supporting and inhibiting factors, and analyze how the changes that have occurred in an integrated manner have resulted in improved results in POPWIL. Using a descriptive qualitative approach with a problem-solving approach, information was obtained through in-depth simulation interviews, monitoring of coaching areas, and analysis of documents related to Sumedang's participation in POPWIL. The research results indicate that Sumedang's basketball coaching progresses through three main stages: incidental, structured change, and networked coaching, which gradually improve the physical readiness, technical-tactical abilities, and psychological resilience of athletes. Improved coaching management, improved facilities, and strengthened coordination between schools, clubs, Perbasi (Indonesian Association of Indonesian Basketball Associations), and the Youth and Sports Agency (Dispora) contributed significantly to this development. This research concludes that Sumedang's improved results in the 2024 POPWIL (Regional Sports Week) were the result of a comprehensive, analytical, and collaborative coaching approach, not simply the result of one-off interventions. These findings provide effective links for the development of sustainable student sports coaching in other regions with similar characteristics.